2001
DOI: 10.1074/jbc.m105076200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Chain Length Dependence of Formation and Dynamics of hMutSα·hMutLα·Heteroduplex Complexes

Abstract: Formation of a ternary complex between human MutS␣, MutL␣, and heteroduplex DNA has been demonstrated by surface plasmon resonance spectroscopy and electrophoretic gel shift methods. Formation of the hMutL␣⅐hMutS␣⅐heteroduplex complex requires a mismatch and ATP hydrolysis, and depends on DNA chain length. Ternary complex formation was supported by a 200-base pair G-T heteroduplex, a 100-base pair substrate was somewhat less effective, and a 41-base pair heteroduplex was inactive. As judged by surface plasmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 36 publications
7
94
0
Order By: Relevance
“…In addition, DNasel footprinting studies reveal that whereas MutS protects approximately one turn of the DNA helix to either side of the mismatch consistent with the crystal structures, the MutS-MutL interaction in the presence of ATP yields a very large DNasel footprint indicative of multiple proteins bound to the DNA (Grilley et al, 1989;Selmane et al, 2003). Formation of a ternary complex involving either the E. coli or human MMR proteins also requires DNA heteroduplexes in excess of 60 bp reflecting multiple binding events in vitro (Blackwell et al, 2001;Plotz et al, 2002;Schofield et al, 2001b). Whether this is an artefact of in vitro conditions or reflects multiple loadings of MMR proteins, either multiple loading of diffusing clamps or cooperative binding of a protein filament, is not definitively established.…”
Section: A Ternary Complexmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, DNasel footprinting studies reveal that whereas MutS protects approximately one turn of the DNA helix to either side of the mismatch consistent with the crystal structures, the MutS-MutL interaction in the presence of ATP yields a very large DNasel footprint indicative of multiple proteins bound to the DNA (Grilley et al, 1989;Selmane et al, 2003). Formation of a ternary complex involving either the E. coli or human MMR proteins also requires DNA heteroduplexes in excess of 60 bp reflecting multiple binding events in vitro (Blackwell et al, 2001;Plotz et al, 2002;Schofield et al, 2001b). Whether this is an artefact of in vitro conditions or reflects multiple loadings of MMR proteins, either multiple loading of diffusing clamps or cooperative binding of a protein filament, is not definitively established.…”
Section: A Ternary Complexmentioning
confidence: 70%
“…ATP-induced dissociation of yMsh2-Msh6 from a mismatch occurs preferentially from DNA ends though direct dissociation from the DNA is also observed Mendillo et al, 2005). Finally, although MutS and MutL (and their eukaryotic homologues) have been observed to form quasi-stable complexes at sites of mismatches in vitro (Blackwell et al, 2001;Räschle et al, 2002;Schofield et al, 2001 b), yeast and human complexes have also been observed to move along the DNA contour in the presence of ATP in surface plasmon resonance experiments (Blackwell et al, 2001;Mendillo et al, 2005).…”
Section: A Ternary Complexmentioning
confidence: 98%
“…Beads were washed three to five times in the same buffer. Five micrograms to 10 µg of GST-hPHF11 or GST alone were incubated with various amounts of RPA or EXO1 protein purified as described previously (Henricksen et al 1994;Blackwell et al 2001) in binding buffer (50 mM HEPES-KOH at pH 7.9, 150 mM NaCl, 1.5 mM MgCl 2 , 0.5% [v/v] NP40, 1 mM DTT, 1 mM PMSF, Roche protease inhibitor mix) for 4-6 h at 4°C. Beads were collected at 500g and washed three times with binding buffer, and bound protein was eluted in 2× Laemmli buffer and analyzed by immunoblotting.…”
Section: Coimmunoprecipitationmentioning
confidence: 99%
“…Mispairs in DNA are recognized by the MutS homodimer in Escherichia coli or by one of two heterodimers of MutS homologs, Msh2-Msh6 or Msh2-Msh3, in eukaryotes (2,10,11). This complex then recruits the MutL homodimer in E. coli or, in eukaryotes, one of two MutL heterodimeric complexes, Mlh1-Pms1 or Mlh1-Mlh3, in an ATP-dependent manner (12)(13)(14)(15)(16). In E. coli, MutS-MutL-DNA ternary complex stimulates the endonucleolytic activity of MutH, which makes single-strand breaks in the unmethylated DNA strand at transiently hemimethylated GATC sites and thus distinguishes the unmethylated daughter DNA strand from the methylated parental DNA strand during and after DNA replication (17)(18)(19).…”
mentioning
confidence: 99%